Trapezoid Multimedia with Visual Thinking Approach to Enhance Achievement of 7th Grade Students - Suarsana, I Made; Nurjanah (Journal of Education Technology, 2023)
The main factual error made by students in solving trapezium problems is the misunderstanding of concepts and principles. Trapezium concepts and principles presented with visual representations may reduce complexity and abstractness compared with relying solely on verbal representations. This study aimed at developing a multimedia trapezium with a visual thinking approach for 7th grade students. This research was development research with 4D design (define, design, develop disseminate). In this first year, research is focused on determining media feasibility based on expert validation, practicality trials, and effectiveness. The subjects involved were material experts, media experts and ten students. Data were collected using validation sheets, questionnaires as well as tests, and analyzed using descriptive statistics. The results of the data analysis showed that the level of feasibility in terms of material experts and media experts were 92% and 88% respectively with the Very Valid category. The practicality and effectiveness test results were 83.7% and 78% in the practical and effective category. Because the media met the valid, practical, and effective criteria, it can be said that the media is suitable to be applied in trapezoidal learning in 7th grade. The implication of implementing visual thinking approach in developing multimedia will be able to enhance students’ achievement.